Outcomes of laparoscopic cholecystectomy in rural hospitals – A systematic review - Farook, Abdul Razack; Kannan, Iyanar; Paul, Sony (Asian Journal of Medical Sciences, 2021)
There are many studies on the laparoscopic cholecystectomy in rural hospitals. It is important to understand whether the advantages of the laparoscopic cholecystectomy are there in the rural hospital set up. The present systematic review of literature aims to find the various outcomes of laparoscopic cholecystectomy in rural hospitals. The study was conducted based on PRISMA guidelines for systematic reviews. The MEDLINE and EMBASE database were used the retrieve the articles. A detailed descriptive analysis was on the various outcomes of open and laparoscopic cholecystectomy. The present systematic review has identified that the laparoscopic cholecystectomy in rural hospitals is most preferred as that of urban setting. It not only provides less hospital stay, but also provides economical option for rural patients. However, there are some limitations in many rural settings like lack of instrumental facility and trained surgeon. The outcomes of the laparoscopic cholecystectomy in some rural hospitals are comparatively same as that of urban settings.